DNA Methylation Tools and Strategies: Methods in a Review - Karbalaie Niya, Mohammad Hadi; Roshan-zamir, Naeimeh; Mortazavi, Elham (Asian Pacific Journal of Cancer Biology, 2019)
DNA methylation is known as an important epigenetic change in plants and vertebrates genome. In this process, the methyl group transferred by DNA methyl transferase enzymes to cytosine at carbon residue 5 often in the CpG dinucleotide context. DNA methylation plays an important role in the natural development of the organism, genome stability maintenance and processes such as genomic imprinting and chromosome X inactivation in mammals. In addition, changes in DNA methylation pattern have seen in many diseases, including cancer. Analysis of DNA methylation has been useful for rapid disease diagnosis and progression. In recent decades, a revolution has taken place in the methods of DNA methylation analysis, and it is possible to study the pattern of gene methylation at a widespread, short and high resolution level. These methods can be divided into three general categories: (1) cut-based methods by methylation-sensitive enzymes; (2) sodium bisulfide based methods; (3) antibody based methods. Since the existence of different methods makes it difficult to select the appropriate approach, in this review, a number of common methods for examining the methylation pattern with the advantages and disadvantages will be discussed.